2017
DOI: 10.18632/oncotarget.23149
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant frizzled1 protein attenuated cardiac hypertrophy after myocardial infarction via the canonical Wnt signaling pathway

Abstract: Postinfarct cardiac hypertrophy is an independent risk factor for heart failure and sudden death. Regression of cardiac hypertrophy has emerged as a promising strategy in the treatment of myocardial infarction (MI). Here we hypothesized that frizzled1 (FZD1), a receptor of the canonical Wnt signaling pathway, is a novel mediator of ischemia-associated cardiac hypertrophy. MI was induced in mice by left anterior descending (LAD) coronary occlusion. One week after MI, the expression of FZD1 was found to be notab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Injection of mice with mouse recombinant FZD-1 protein leads to an immune response against the FZD-1 receptor, attenuating the induction of FZD-1 expression in infarcted mice. Nevertheless, this approach did not confer any effect on infarct size, even though CM hypertrophy was attenuated in immunized mice [ 40 ]. Our group used a different approach in order to target the FZD receptors.…”
Section: Effect Of Interventions In Wnt Signaling On Infarct Sizementioning
confidence: 99%
“…Injection of mice with mouse recombinant FZD-1 protein leads to an immune response against the FZD-1 receptor, attenuating the induction of FZD-1 expression in infarcted mice. Nevertheless, this approach did not confer any effect on infarct size, even though CM hypertrophy was attenuated in immunized mice [ 40 ]. Our group used a different approach in order to target the FZD receptors.…”
Section: Effect Of Interventions In Wnt Signaling On Infarct Sizementioning
confidence: 99%
“…Compared with a prevalence of less than 20% in the general population, cardiac hypertrophy affects up to 70% of patients during moderate CKD and approaches 90% of patients on dialysis (40). Although elevated FGF23 is associated with cardiac hypertrophy, the extent of soft tissue calcifications (41), anemia (42), tissue hypoxia (43), inflammation (44), and paracrine/autocrine factors such as Wnt-related proteins and other FGFs (45,46), which likely play significant roles, remains to be determined. Thus, the complete functions of FGF23 in maintaining mineral homeostasis, as well as its potential crosstalk with other metabolic systems in CKD, are not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…In addition correlation between miR‐17‐5p and circ‐ITCH revealed that miR‐17‐5p could restore the protective functions of circ‐ITCH in myocardial cells. According to previous studies, Wnt/β‐catenin signalling pathway could accelerate process of cardiovascular diseases 39 , 40 . In this study, we also measured proteins in the Wnt/β‐catenin signalling pathway, which revealed that Wnt3a, Wnt5a and β‐catenin levels were all upregulated.…”
Section: Discussionmentioning
confidence: 93%
“…According to previous studies, Wnt/β-catenin signalling pathway could accelerate process of cardiovascular diseases. 39,40 In this study, we also measured proteins in the Wnt/β-catenin signalling pathway, which revealed that Wnt3a, Wnt5a and β-catenin levels were all upregulated. After Wnt inhibitor, NCB-0846 was applied, levels of Wnt3a, Wnt5a and β-catenin were decreased, which upregulated viability of H9c2 cells as well as ATP concentrations and suppressed apoptosis rate and related protein expression.…”
Section: Discussionmentioning
confidence: 98%